IMPLEMENTASI NILAI-NILAI KEARIFAN LOKAL GOTONG ROYONG DALAM PEMBELAJARAN SEJARAH1 - Pamungkas, Sumaryono Karyo; Isawati, Isawati; Yuniyanto, Tri (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
This study aims to determine (1) Understanding of history teachers and students about the values of local wisdom gotong royong in MAN 1 Surakarta; (2) Planning, implementation, constraint, and evaluation done in implementing the values of local wisdom of gotong royong in learning history of class XI IPA 2 in MAN 1 Surakarta academic year 2016/2017.This study used descriptive qualitative method. Source of data comes from informants, events and places, as well as documents. Data were collected through interviews, observation, and document analysis. Validity test is done by using triangulation data and triangulation method. Data analysis techniques using interactive analysis techniques consisting of data collection, data reduction, data presentation, and conclusion.The results of the research show that (1) the understanding of the history teacher about the values of local wisdom gotong royong has understood the understanding of gotong royong in general, but in its application the teacher can not create the maximum learning history. While the students' understanding of the values of local wisdom gotong royong only understand the understanding of mutual cooperation in general, lack understanding of the essence of mutual cooperation; (2) Planning the implementation of the values of local wisdom gotong royong in learning history has been listed in the RPP and implemented through learning activities in the classroom and follow through daily life both in the school environment and in the dormitory environment; (3) Obstacles encountered include: (a) Less historical learning hours, (b) Student interest in history lesson, (c) When many student learning leave the lesson because there are school activities that need to be resolved, (d) Egos of students who are clever not willing to merge with students who are less intelligent; (4) Evaluation is done through the assessment of cognitive, affective, and psychomotor aspects.